Korean Residents' Experiences of Racism in Germany During the COVID-19 Pandemic: Association with Life Satisfaction and Sense of Belonging - Joohyun Justine Park; Ah-Hyun Angela Lee; Lynne Soon-Chean Park; Rebekah Jaung; Changzoo Song (Journal of International Migration and Integration, 2024)
Since the outbreak of COVID-19, more incidents of anti-Asian racism have been reported in Europe. Asians in Germany have been directly and indirectly exposed to racism, with potential implications for their well-being and sense of belonging. This study aimed to explore racism experiences among Korean residents in Germany since the outset of the pandemic. It also examines how racism is associated with their life satisfaction and sense of belonging to the host society. Our online survey of 552 Koreans residing in Germany shows that since the beginning of the pandemic nearly 80% of them experienced direct and/or indirect racism mainly in public places, public transportation, social media, and mainstream media. Women, younger people, and temporary visa-holders were more likely to experience racism than other groups. While the experience(s) of racism was associated with lower life satisfaction, a stronger sense of belonging to local communities and German society as a whole appeared to alleviate the negative effect of the racism experience. This study shows the pervasiveness of anti-Asian racism in Germany, and thus urges German society and local communities to commit to creating inclusive and diverse environments alongside anti-racism efforts.
Keywords: 300; Racism experience; Life satisfaction; A sense of belonging; Korean residents in Germany; Anti-Asian racism; COVID-19 pandemic